STUDI PENERAPAN PENDEKATAN COMMUNITY LED ASSESSMENT AND PLANNING PROCESS (CLAPP-GPI) DALAM PENYUSUNAN PERENCANAAN PEMBANGUNAN DESA (RPJM-DESA) DI KABUPATEN BANTAENG - Syamsu Alam (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
The purpose of this study was to describe the variable / information on the application-GPI CLAAP approach in the preparation of its medium-Village at 3 in the sample villages Bantaeng. This research is a descriptive study with qualitative approach in this case using inductive logic thinking. findings obtained through connecting, Indexing and interpretation of data / information obtained from in-depth interviews and Focus Group Discussion (FGD). From the results of the study concluded that: (1) In general penegetahuan village community (village government, Village Facilitators and Villagers) on the approximation of Clapp-GPI, related sense, the importance berfocus on the poor and women (GPI) and principles / basic values Clapp-GPI memuskan enough. (2) The survey results also showed that approximately 76.7% - 86.7% of respondents were very satisfied with the benefits of planning Rural Development in identifying and identifies poverty according to the perspective of the local community. (3) The survey results also showed that in general the respondents were satisfied and very satisfied with the application of the Clapp-GPI in the preparation of village plans-RKP Village beneficial to the improvement of quality of life, help to improve the quality of rural development planning, help in accessing and managing programs and kedesa budget entry